Block Copolymers of Ethylene Oxide and Propylene Oxide: Prospects for Medical and Pharmaceutical Application in Russia - E. O. Bakhrushina; V. S. Pyzhov; P. S. Sakharova; N. B. Demina; D. A. Chizhova; T. V. Tabanskaya; M. F. Lutfullin (Регуляторные исследования и экспертиза лекарственных средств, 2023)
Block copolymers of ethylene oxide and propylene oxide (EO/PO block copolymers) are polymeric non-ionic surfactants with a high hydrophilic–lipophilic balance also referred to as pluronics, poloxamers, or proxanols. These compounds are among the most demanded modern excipients for the production of medicines. EO/PO block copolymers are used both in the production of traditional (liquid, semi-solid, and solid) dosage forms and as part of targeted delivery systems. The extensive application of EO/PO block copolymers is due to the diverse array of their properties, including not only solubilising, emulsifying, gelling, and other effects but also thermoreversibility, which is essential for developing in situ delivery systems and 3D printing technologies.The aim of the study was to evaluate the potential of EO/PO block copolymers for medicinal use and to assess the range of medicinal products approved in the Russian Federation that contain EO/PO block copolymers.This review presents an analysis of the register of poloxamer-containing medicines approved in the Russian Federation, a list of the largest manufacturers of EO/PO block copolymers in the world, and a study of the possibility to use copolymers for medical purposes. Currently, there are more than 10 chemical manufacturers producing EO/PO block copolymers for the pharmaceutical, biotechnology, and other industries around the world. EO/PO block copolymers are included in more than 60 medicinal products present in the Russian pharmaceutical market; this observation indicates the need to phase out the import of poloxamers.